Standardized phytopreparations and cucurbitacin IIb from Ibervillea sonorae (S. Watson) greene induce apoptosis in cervical cancer cells by Nrf2 inhibition - Vidal-Gutiérrez, Max [UNESP]; Torres-Moreno, Heriberto; Arenas-Luna, Víctor; Loredo-Mendoza, María Lilia; Tejeda-Dominguez, Farid; Velazquez, Carlos; Vilegas, Wagner [UNESP]; Hernández-Gutiérrez, Salomón; Robles-Zepeda, Ramón E. (Elsevier, 2022)
Ethnopharmacology relevance: Ibervillea sonorae (S. Watson) Greene is a plant from northwestern Mexico, known as “Wereke” or “Guareque”, used by the Mayo ethnic group to treat diabetes and cancer. Cucurbitacin IIb (CIIb), isolated from I. sonorae has apoptotic and antitumor activity in a model of cervical cancer with the HeLa cell line. One pathway affected by cucurbitacins is Nrf2, a glutathione transferase (GST) transcription factor, important in the regulation of mitochondrial oxidative stress (MOS). A signal of MOS is the change in the mitochondrial membrane potential (ΔΨm), which has been detected in HeLa in the presence of CIIb. Fito-Ison-EtOH (Etanison) and Fito-Ison-EtOAc (Acetison) are phytopreparations from I. sonorae standardized according to their CIIb content (6.7 mg/g and 18.4 mg/g of CIIb, respectively). Etanison and Acetison have been reported to induce morphological changes in HeLa like those induced by CIIb. Aim of the study: To evaluate the apoptotic and Nrf2 inhibition activity of the phytopreparations Acetison and Etanison from Ibervillea Sonorae in the HeLa cervical cancer cell line. Materials and methods: Antiproliferative activity was evaluated by the MTT method at 24, 48, and 72 h. For Acetison and Etanison, serial concentrations from 6.25 μg/mL to 100 μg/mL were tested, and for CIIb from 1.56 μg/mL to 50 μg/mL. The expression of Nrf2, caspase 3, and caspase 9 was evaluated by western blot, using concentrations of 30 μg/mL for Acetison, 50 μg/mL for Etanison, and 15 μg/mL for CIIb. Cisplatin was used as a positive control. Results and conclusions: Apoptotic activity of Etanison and Acetison was demonstrated in HeLa, due to the presence of caspase-9 and caspase-3 in western blot assays. Likewise, both the phytopreparations and CIIb showed inhibition of Nrf2, associating apoptotic activity with the inhibition of the GST transcription factor. In this sense, the phytopreparations of I. sonorae, as well as their derivatives, have the potential to obtain and develop anticancer products.
Keywords: Apoptosis; Cucurbitacin IIb; Ibervillea sonorae; Nrf2; Phytopreparations